The impact of assessment time limits on accounting students’ integration of technical accounting knowledge with higher-order thinking skills - Stiglingh, M. (Madeleine) (University of Pretoria, 2025)
Thesis (PhD (Accounting Sciences))--University of Pretoria, 2025.